Characteristics of Gastronomic Brands of the Republic of Uzbekistan and Their Place in the Tourism and Hospitality Market (Zien Journal of Social Sciences and Humanities, 2023)
The article discusses the importance of the development of the tourism industry, which contributes to solving a large number of problems connected with the forming GDP of the country, employment, the creation of additional jobs, the opening of enterprises, socio-economic development of individual regions. Local regional cuisine is one of the factors that can be attractive for tourists. The basis of gastronomic tourism is the food industry and culinary peculiarities of a certain country, which is often the so-called "tourist magnet". Regional cuisine is one of the promising directions in increasing the efficiency of this type of tourism. Gastronomic tourism is relevant at all times and there is a real demand for it.